2019
DOI: 10.1002/pa.2024
|View full text |Cite
|
Sign up to set email alerts
|

Does access to domestic finance and international finance contribute to sustainable development goals? Implications for policymakers

Abstract: Seventeen goals presented by the United Nation General Assembly provide an evidence‐based framework of planning and programming for sustainable development goals (SDGs) until 2030. There is a growing catalog of related reviews, recommendations, advice, and publications, whereas the professional community is undoubtedly emphasizing the need to adopt evidence‐based methodologies for the implementation of SDGs. In particular, emerging economies face a big challenge to implement SDGs practices efficiently. Some co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
41
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(42 citation statements)
references
References 53 publications
1
41
0
Order By: Relevance
“…However, the business organizations have now realized the importance of environmental and nonfinancial performance because of the community pressure and governmental regulations (Ilyas et al 2020;Memon et al 2020). Consequently, several strategies have been introduced to gain desirable environmental, financial and nonfinancial performance namely modern technology (Chege and Wang 2020;Singh et al 2019), financial resources (Khattak 2020;Memon et al 2020), intellectual capital (Demartini and Beretta 2020), entrepreneurial orientation (Amankwah-Amoah et al 2019), knowledge management (Kmieciak and Michna 2018;Roxas and Chadee 2016) and enterprise risk management (ERM) (Brustbauer 2016;, all of which are found to be relevant and equally important but the ERM in particular has become a key predictor of performance in financial institutions because they are persistently engaged in the reduction of financial loss and risk (Rasid et al 2014). As an emphasis, after the 2007-2008 financial crises, most banks and financial institutions established a formal ERM framework to mitigate potential risk (Adedayo et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…However, the business organizations have now realized the importance of environmental and nonfinancial performance because of the community pressure and governmental regulations (Ilyas et al 2020;Memon et al 2020). Consequently, several strategies have been introduced to gain desirable environmental, financial and nonfinancial performance namely modern technology (Chege and Wang 2020;Singh et al 2019), financial resources (Khattak 2020;Memon et al 2020), intellectual capital (Demartini and Beretta 2020), entrepreneurial orientation (Amankwah-Amoah et al 2019), knowledge management (Kmieciak and Michna 2018;Roxas and Chadee 2016) and enterprise risk management (ERM) (Brustbauer 2016;, all of which are found to be relevant and equally important but the ERM in particular has become a key predictor of performance in financial institutions because they are persistently engaged in the reduction of financial loss and risk (Rasid et al 2014). As an emphasis, after the 2007-2008 financial crises, most banks and financial institutions established a formal ERM framework to mitigate potential risk (Adedayo et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Studies have examined how financial capital is one of the significant factors of social and environmental practices (Hasan & Habib 2017;Ruggiero & Cupertino, 2018;Scholtens, 2006). In contrast, firms with a lack of financial resources are less likely to participate in social and environmental activities (Khattak, 2020). Surprisingly, entrepreneurial finance in CSR and environmental practices has remained mostly untouched as an issue, specifically when it comes to emerging firms.…”
mentioning
confidence: 99%
“…Moreover, it is argued that managers with high levels of education might strive to achieve more social practices as a result of their awareness of and knowledge about social efforts and their benefits. Consequently, studies in the same vein have also suggested these factors as controls when examining SMEs’ performance, outputs, and consequences (Anwar, 2018; Khan et al, 2020; Khattak, 2020). In our results, we found mixed results for these controls (see the findings of the structural model).…”
Section: Methodsmentioning
confidence: 99%